Motor ability in children treated for idiopathic clubfoot. A controlled pilot study - Westbom Lena; Andriesse Hanneke; Hägglund Gunnar (BMC, 2009)
Abstract Background To study motor ability at seven years of age in children treated for idiopathic clubfoot and its relation to clubfoot laterality, foot status and the amount of surgery performed. Methods Twenty children (mean age 7.5 years, SD 3.2 months) from a consecutive birth cohort from our hospital catchments area (300.000 inhabitants from southern Sweden) were assessed with the Movement Assessment Battery for Children (MABC) and the Clubfoot Assessment Protocol (CAP). Results Compared to typically developing children an increased prevalence of motor impairment was found regarding both the total score for MABC (p < 0.05) and the subtest ABC-Ball skills (p < 0.05). No relationship was found between the child's actual foot status, laterality or the extent of foot surgery with the motor ability as measured with MABC. Only the CAP item "one-leg stand" correlated significantly with the MABC (rs = -0.53, p = 0.02). Conclusions Children with idiopathic clubfoot appear to have an increased risk of motor activity limitations and it is possible that other factors, independent of the clinical status, might be involved. The ability to keep balance on one leg may be a sufficient tool for determining which children in the orthopedic setting should be more thoroughly evaluated regarding their neuromotor functioning.